EFFECT OF AIR AND SOAKING OF NaCl SOLUTION ON CORROSION RATE OF S45C STEEL WELDS - Akhmad Syarief; Ade Azhari Rahmatuloh (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2020)
Welding is the joining of two metals so that a strong connection is formed. One of the causes of this steel's efficiency is decreasing. Corrosion is a decrease in the quality and quality of material due to chemical reactions with elements in the environment. The purpose of this study was to determine the effect of air and immersion of NaCl solution on the corrosion rate. The method used is the weight loss method, where after 38 days the S45C steel is left in the open space and 38 days left in the NaCl solution with a variation of seam V, ½ V, and I. From the results of testing for 38 days, the highest corrosion rate of welded seam variation in NaCl solution was 0.0644 mm/y, and then ½ V was 0.0635 mm/y, and the lowest was seam V with 0.0631 mm/y Whereas, without immersion, the highest corrosion rate in seam I was 0.00488 mm/y, followed by ½ V with 0.00431 mm/y, and the lowest seam V was 0.00429 mm/y, V with 0.00431 mm/y, and the lowest seam V with 0.00429 mm/y.